1994
DOI: 10.3109/17453679408995462
|View full text |Cite
|
Sign up to set email alerts
|

Osseointegration of titanium implants in the tibia: Electron microscopy of biopsies from 4 patients

Abstract: We studied the ultrastructure of bone tissue around implants of pure titanium inserted into the tibia in 4 patients with arthrosis or rheumatoid arthritis. Three main appearances of the interface were noted. First, a close contact between titanium and calcified bone with living osteocytes inside the newly-formed bone was observed in all samples. Secondly, a close contact was also seen between the implant and osteoid, the newly formed collagenous matrix being either uncalcified or calcifying. Thirdly, a loose e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 13 publications
(7 reference statements)
0
11
0
Order By: Relevance
“…This more or less amorphous layer seems to constitute one part of the interface and can contribute to the nonelastic behavior of the interface. Mineralized bone has been reported to be in direct contact with the implant surface (21); hence, the anatomy of the interface is complex.…”
Section: Discussionmentioning
confidence: 99%
“…This more or less amorphous layer seems to constitute one part of the interface and can contribute to the nonelastic behavior of the interface. Mineralized bone has been reported to be in direct contact with the implant surface (21); hence, the anatomy of the interface is complex.…”
Section: Discussionmentioning
confidence: 99%
“…Through the presence of osteocytes adjacent to the implant surface after prolonged healing periods, early investigators demonstrated that peri-implant bone around metals is indeed a living tissue ( Serre et al 1994 ). The inner wall of the osteocyte lacuna exhibits basophilic staining properties similar to the osteoid-like matrix interposed between mineralized bone and the implant surface ( Piattelli et al 1994 ).…”
Section: Osteocytes and Implant Biomaterialsmentioning
confidence: 99%
“…Biocompatibility . The biological response to titanium and cobalt-chrome alloys have been studied extensively and their biocompatibility has been demonstrated to be favorable 45,46,207,348 . In an early study, Brånemark described the concept of osseointegration and suggested that direct contact between titanium implants and bone at LM Biomaterials level was achieved 30,31 .…”
Section: Metalsmentioning
confidence: 99%